Light-triggered in vivo activation of adhesive peptides regulates cell adhesion, inflammation and vascularization of biomaterials - Lee, Ted T.; García, José R.; Paez, Julieta I.; Singh, Ankur; Phelps, Edward A.; Weis, Simone; Shafiq, Zahid; Shekaran, Asha; del Campo, Aránzazu; García, Andrés J. (Nature materials, 2015)
Materials engineered to elicit targeted cellular responses in regenerative medicine must display bioligands with precise spatial and temporal control. Although materials with temporally regulated presentation of bioadhesive ligands using external triggers, such as light and electric fields, have recently been realized for cells in culture, the impact of in vivo temporal ligand presentation on cell–material responses is unknown. Here, we present a general strategy to temporally and spatially control the in vivo presentation of bioligands using cell-adhesive peptides with a protecting group that can be easily removed via transdermal light exposure to render the peptide fully active. We demonstrate that non-invasive, transdermal time-regulated activation of cell-adhesive RGD peptide on implanted biomaterials regulates in vivo cell adhesion, inflammation, fibrous encapsulation, and vascularization of the material. This work shows that triggered in vivo presentation of bioligands can be harnessed to direct tissue reparative responses associated with implanted biomaterials. Transdermal light-triggered activation of cell-adhesive peptides on the surface of implanted hydrogels alters cell–material interactions, such as cell adhesion and spatial patterning, and fibrous encapsulation and vascularization of the material.